Preparation and Characterization of Low- emissivity AlN/Ag/AlN Films by Magnetron Cosputtering Method - Wuttichai Phae-ngam; Surachart Kamoldilok; Tanattha Rattana; Tossaporn Lertvanithphol; Araya Mungchamnankit (My University, 2023)
AlN and Ag thin films were deposited independently on the Si(100) wafers and glass slides by sputtering techniqueat various times to find the optimum deposition times for coating AlN and Ag films layers. The results obtained fromglazing-incident X-ray diffraction (GIXRD), field-emission scanning electron microscopy (FE-SEM), and transmittancemeasurements showed that the optimum deposition time for coating AlN and Ag film layers were 40 min and 15 scorresponding to the film thickness of 46.7 and 19.6 nm, respectively. The optimum deposition times were used forcoating AlN and Ag films in the multilayer AlN/Ag/AlN film stack. Then, the multilayer AlN/Ag/AlN film stack wasdeposited on the glass slide for transmittance measurement and a test glass plate with a size of 10 cm x 10 cm for infraredprotection testing. The average solar transmittances in the visible range ( = 380-780 nm) and in the near infrared range( = 780-2,000 nm) were found to be 48.05 and 15.17%, respectively which are comparable with those of a commercialglass.
Keywords: Deposition; GaN-based semiconductor devices and materials